Development of networked games for handheld personal devices - Yessekeyev, Rustem. (2010)
This report presents the on-going development of multiplayer Internet game based on the Service-Oriented HLA RTI (SOHR) framework. Service-Oriented HLA RTI is an implementation of the High Level Architecture (HLA).